The Effect of Supervision, Career Development, and Position Promotion on Employee Performance at PT. Saka Partner Sejati Medan - Syafriadi (Jurnal Mantik, 2021)
Research with the title "The Effect of Supervision, Career Development, and Promotion of Position on Employee Performance at PT. Saka Mitra Sejati Medan” This study aims to explain the influence of the variables of Supervision, Career Development, and Position Promotion simultaneously and partially on Employee Performance at PT. Saka Mitra Sejati Medan. The research method used is a quantitative model, using a questionnaire as a data collection tool which is distributed to all units/sections of PT. Saka Mitra Sejati Medan, totaling 67 employees. Analysis of the data in this study using multiple linear regression analysis assisted by a computer program SPSS for Windows. The results of the simultaneous test resulted in the F test yielding a calculated F value of 21,458 with a significant level of 0.00. Because F count 21,458 > F table 2.75 and the significant probability is much smaller than 0.05, i.e. 0.00 < 0.05, the regression model for the variables of supervision, career development, and promotion can be said that together they have a positive effect. significant to the performance of employees of PT. Saka Mitra Sejati Medan. The results of the test of the control variable t count 3.616 > t table 1.669 with a significant 0.000 <0.05, meaning that partially the supervision variable has a positive and significant effect on the performance of employees of PT. Saka Mitra Sejati Medan. The results of the career development variable test value t count 1.675 > t table 1.669 with a significant 0.000 > 0.050, meaning that partially career development variables have a positive and significant effect on the performance of employees of PT. Saka Mitra Sejati Medan. The results of the job promotion variable test value tcount 2,335 > ttable 1,669 with a significant 0.000 < 0.050, meaning that partially the job promotion variable has a positive and significant effect on the performance of PT. Saka Mitra Sejati Medan. The number of Adjusted R Square is 0.482, which means that 48.2% of the dependent variable is the performance of PT. Saka Mitra Sejati Medan is explained by independent variables consisting of supervision, career development, and promotion, and the remaining 51.8% is explained by other variables outside of the variables used. So most of the dependent variables are explained by the independent variables used in the model.